The influence of mindfulness and Buddhist rituals on the spirituality of students at STAB Maitreyawira Pekanbaru - Dharmaji Chowmas; Adi W Gunawan; Sutikyanto (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
The background of this study was the importance of the role of spirituality for students as the young generation. Nowadays, students experience academic stress, reducing academic achievement, reducing motivation, and increasing the risk of dropping out of school. This study was conducted to obtain an overview of the influence of mindfulness and Buddhist religious rituals on students' spirituality. The sample for this study was 106 students at STAB Maitreyawira Pekanbaru, which consisted of 3 batches, namely 2020, 2019, and 2018 batches. The data collection instrument was a closed questionnaire. This study was done quantitatively and analyzed by Pearson correlation test and multiple regression analysis. The results of data analysis showed that the higher the awareness and the higher the Buddhist religious rituals, the higher the spirituality of students at STAB Maitreyawira Pekanbaru and vice versa. This study concluded that students' spirituality could be improved through increased mindfulness and Buddhist religious rituals, either individually (alone) or jointly (together).